Retrospective Evaluation of Twenty Seven Patients with Diabetic Foot Infection - Sevtap Şenoğlu; Şemsi Nur Karabela; Kadriye Kart Yaşar; Bülent Durdu; Habip Gedik; Birsen Ersöz; Vesile Şahin; Nuray Güleç (Haseki Tıp Bülteni, 2017)
Aim: This study analyzed diabetic foot infections (DFI) in patients who were followed up in our clinic. Methods: We retrospectively evaluated demographic characteristics and clinical and laboratory findings in 27 patients (12 female, 15 male) with DFI who were followed up in our clinic between June 2013 and January 2014. The foot ulcerations in the patients were classified according to Wagner’s classification. Results: The mean age of the patients was 59 years. Erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) and white blood cell levels were found to be high in 89%, 78% and only 22% of patients, respectively. 78% of patients had grade 2 and lower grade ulcerations. Growth of methicillin-resistant Staphylococcus aureus, Enterobacter cloacae and Enterococcus spp. was encountered in five (28%) of 18 patients in whom deep tissue culture test could be performed. Conclusion: Appropriate diagnosis and treatment planning can be achieved by guiding classifications performed by regarding clinical, neurological and vascular conditions as well as ulcer depth. In follow-up of cases, ESR and CRP tests are very useful in diagnosis and treatment of the complications such as osteomyelitis, which may lead to amputation. Treatment should be conducted with a multidisciplinary approach in tertiary healthcare facilities.